Perancangan Ulang Tata Letak Fasilitas Gudang Klinik XYZ Menggunakan Metode Dedicated Storage - Cuincen Faturendra Siboro; Erni Yusnita (INVENTORY: Industrial Vocational E-Journal On Agroindustry, 2021)
In a warehouse facility layout design including a health clinic, the layout design of warehouse facilities and production storage areas plays a very important role, it is impossible for the manufactured goods to be distributed directly to all customers. For this reason, there is a need for a good storage area and storage system to simplify the production process. Clinic XYZ is a 24-hour public health clinic, located in a sub-district in North Sumatra, to be precise in Medan Deli District. The problem that occurs is the random arrangement of goods in the warehouse without paying attention to storage and arrangement patterns that depend on the position of the empty warehouse. Based on observations, it is known that the time span needed to look for drugs at the clinic is too long, so this will make it difficult for employees / operators to manage the products to be stored or retrieved from the drug warehouse. One of the warehouse design methods that can be used is the dedicated storage method. Dedicated storage is a method of placing a specific location or storage area for each item stored. In this study, the types of drugs were classified into drugs, solid types of drugs, semi-solid drugs, liquid drugs and gas drugs. Based on the results obtained, the number of slots needed in the drug product warehouse is 11 slots, the total floor area needed is 13.2 m2, the area needed for storing medicinal products with an alley area is 6.8 m2, the percentage of area that is not used for storage the product in the medicinal product warehouse is 34% and the diagonal length of the hand truck when carrying the box is 1.56 m.